Cover Picture: Design and Synthesis of Selurampanel, a Novel Orally Active and Competitive AMPA Receptor Antagonist (ChemMedChem 3/2017). (3rd February 2017) - Orain, David; Tasdelen, Engin; Haessig, Samuel; Koller, Manuel; Picard, Anne; Dubois, Celine; Lingenhoehl, Kurt; Desrayaud, Sandrine; Floersheim, Phillip; Carcache, David; Urwyler, Stephan; Kallen, Joerg; et al.
Abstract : The front cover picture shows the modulation of hGluA2 by Selurampanel (central structure), a novel α‐amino‐3‐hydroxy‐5‐methyl‐4‐isoxazolepropionic acid (AMPA) receptor antagonist. hGluA2 is a member of the AMPA receptor family (lower right). This receptor mediates fast excitatory neurotransmission and is linked with a variety of neurodegenerative and psychiatric diseases. Overstimulation of these receptors plays a role in triggering seizures associated with epilepsy (represented by the green epileptiform discharge signal). AMPA receptor antagonists are currently in clinical development as anti‐epileptic drugs (AEDs) and there is evidence from various sources that this mechanism of action is of therapeutic use in epilepsy. More information can be found in the Communication by Henri Mattes et al. onpage 197 in Issue 3, 2017 (DOI:10.1002/cmdc.201600467 ). (Graphics by Alan Abrams.)